Motivation for risk information seeking among hospital employees in the context of COVID-19 pandemic: an organisational perspective - Law, Yee Chin; Tham, Jen Sern; Wee, Tong Ming; Kasimon, Diyana Nawar (Penerbit Universiti Kebangsaan Malaysia, 2024)
The outbreak of novel infectious diseases like COVID-19 elicits widespread uncertainty and fear, prompting individuals to seek information from various media channels to protect themselves and their loved ones. However, the factors that motivate hospital employees, who serve as the frontliners in combating the COVID-19 pandemic, to seek COVID-19-related information are still far from understood. Guided by the Risk Information Seeking and Processing (RISP) model, this study aimed to examine the motivational factors that drive hospital employees' risk information-seeking behaviour within the Malaysian context. Through analysis of a proportionate stratified sample size of hospital employees (N=407), this study revealed that information needs, current knowledge, and organisational norms significantly influence hospital employees' intention to seek risk information. These findings contribute to the theoretical development of the RISP model by highlighting theimportance of information needs as a prominent factor and underscoring the valuable role of organisational norms in shaping hospital employees' risk information-seeking behaviour within hospital settings. From a practical standpoint, our findings offer valuable insights that can inform communication strategies and enhance organisational support in healthcare environments, particularly in risk management. By considering our results, healthcare institutions can improve their preparedness for future pandemics and strengthen risk communication within Malaysia's healthcare system. Furthermore, this study extends the application of the RISP model and related work within the COVID-19 pandemic, providing pertinent knowledge on risk communication within the healthcare sector.